PENGEMBANGAN DESAIN PEMBELAJARAN ICARE BERBANTUAN LEARNING MANAGEMENT SYSTEM UNTUK MENINGKATKAN PROSES PEMBELAJARAN - Aulia, Fikri (EDUTECH, 2017)
Abstract. Learning is a process of education conducted by the teacher to the learner, the learning will be more effective when utilizing media. The development of information and communication technologies have an important role in learning. In addition to media, instructional design is also influential in the learning process. In this study, researchers are interested in researching the development of ICT-assisted with learning design to improve the effectiveness of learning. This research aims to find hipotetik model of instructional design development ICARE assisted learning management system to improve the learning process, in addition to knowing their effectiveness. This type of research is research and development. Defined by the Borg and Gall (2003), that "educational research and development is a process used to develop and validate educational products". Further they also suggested 10 measures of research and development, which can be simplified into the following five main steps: (1) conduct an analysis of the product to be developed; (2) develop the initial product; (3) expert validation and revision; (4) small scale field trial and revision products; (5) large scale field tests and the final product. Researchers recommend that (1) the application of instructional design ICARE-assisted Learning Management System should need to be developed to became a blended learning are more effective, (2) the findings in this research so that it can be used more broadly.Keywords: Instructional Design ICARE, Learning Management System, Learning ProcessAbstrak. Pembelajaran merupakan proses pendidikan yang dilakukan oleh pengajar kepada peserta didik, pembelajaran akan lebih efektif apabila memanfaatkan media. Perkembangan Teknologi Informasi dan Komunikasi memiliki peran penting dalam pembelajaran. Selain media, desain pembelajaranpun akan berpengaruh dalam proses pembelajaran. Dalam penelitian ini, peneliti tertarik untuk meneliti pengembangan desain pembelajaran dengan berbantuan TIK untuk meningkatkan keefektifan pembelajaran. Penelitian ini bertujuan untuk menemukan model hipotetik tentang pengembangan desain pembelajaran ICARE berbantuan learning management system untuk meningkatkan proses pembelajaran, selain itu untuk mengetahui keefektifannya. Jenis penelitian ini adalah penelitian dan pengembangan. Ditegaskan oleh Borg dan Gall (2003), bahwa â€œeducational research and development is a process used to develop and validate educational productsâ€. Lebih lanjut mereka pun mengemukakan 10 langkah penelitian dan pengembangan, yang dapat disederhanakan menjadi lima langkah utama berikut: (1) melakukan analisis produk yang akan dikembangkan; (2) mengembangkan produk awal; (3) validasi ahli dan revisi; (4) ujicoba lapangan skala kecil dan revisi produk; (5) ujicoba lapangan skala besar dan produk akhir. Peneliti menyarankan (1) penerapan desain pembelajaran ICARE ber-bantuan Learning Management System hendaknya perlu dikembangkan agar tercipta pembelajaran blended (blended learning) yang lebih efektif, (2) temuan dalam penelitian ini agar dapat diakomodir secara lebih luas.Kata Kunci : Desain Pembelajaran ICARE, Learning Management System, Proses Pembela-jaran